Bone formation and growth of climbing perch Anabas testudinieus larvae fed with Zn enriched Artemia nauplii - Ismarica Ismarica; Mia Setiawati; Dedi Jusadi; Muhammad Agus Suprayudi (Jurnal Akuakultur Indonesia)
ABSTRACT